En route to disentangle the impact and neurobiological substrates of early vocalizations: Learning from Rett syndrome - Marschik, P.; Kaufmann, W.; Bölte, Sven; Sigafoos, J.; Einspieler, C. (Cambridge University Press, 2014)
Research on acoustic communication and its underlying neurobiological substrates has led to new insights about the functioning of central pattern generators (CPGs). CPG-related atypicalities may point to brainstem irregularities rather than cortical malfunctions for early vocalizations/babbling. The vocal pattern generator, together with other CPGs, seems to have great potential in disentangling neurodevelopmental disorders and potentially predict neurological development.